2021
DOI: 10.3389/fpsyg.2021.723171
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Suggestion Feedback Facilitates Creativity of Students in STEAM Education

Abstract: This study examined the influence of the formative feedback types of teachers on creativity in Science, Technology, Engineering, Art, Mathematics (STEAM) education. Participants were 90 undergraduate students who were randomly assigned to the teacher opinions feedback group, the teacher suggestion feedback group, or the non-feedback group, and took part in three courses of STEAM education of 3D-printing technology. Before and after each course, they were asked to fill out the Eugene Creativity Test. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In SDG4, there is a greater focus on quality education and the promotion of lifelong learning and development for all ( UN, 2020 ). Shen et al (2021) stated that students can develop higher-order thinking as well as competency-based literacy in STEAM activities. Furthermore, Ültay and Ültay (2020) stated that teacher education students are considered an important group for educational sustainability and that engaging in more STEAM activities can help them acquire 21st century skills such as collaboration and innovation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In SDG4, there is a greater focus on quality education and the promotion of lifelong learning and development for all ( UN, 2020 ). Shen et al (2021) stated that students can develop higher-order thinking as well as competency-based literacy in STEAM activities. Furthermore, Ültay and Ültay (2020) stated that teacher education students are considered an important group for educational sustainability and that engaging in more STEAM activities can help them acquire 21st century skills such as collaboration and innovation.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a study by Wen et al (2020) found that students with better learning performance in a guided inquiry learning environment were more actively engaged in inquiry activities and demonstrated good scientific literacy. STEAM education, on the other hand, is a multidisciplinary approach that emphasizes the development of higher-order thinking and competencies ( Shen et al, 2021 ), with more emphasis on hands-on activities that promote the development of sustainable inquiry behaviors ( Rahmawati et al, 2022 ). In addition, in the process of educational sustainability, teacher education students need to promote the development of their collaborative, creative, and thinking skills through STEAM learning ( Ültay and Ültay, 2020 ), and to improve their learning performance through course work that better promotes continuous inquiry behaviors.…”
Section: Research Hypothesis and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Creativity is producing or creating something new and in a unique way (Torrance, 1970). Whereas, creativity is defined as the ability or capability to create original creative power as well as develop new ideas and accordingly (Shen et al, 2021). Moreover, creativity is the ability to produce a work that has 'novelty' or has new elements in the work as well as original ideas, not expected by others and appropriate (Zhou Kai, 2018).…”
Section: Creativitymentioning
confidence: 99%
“…Creativity skills can improve academic performance and develop children's talents as well as build innovative thinking processes (UNICEF, 2015). Creativity skills are the ability or capability to produce something new and useful (Shen et al, 2021). Nowadays, creativity skills are no longer optional skills whereas creativity skills become a necessity for the younger generation (Agnoli et al, 2018).…”
Section: Creativitymentioning
confidence: 99%